Ion-implantation-induced disorder in FePt-C thin films - Kumar, Durgesh (2021)
The effects of ion implantation through a mask on the structural and magnetic properties of FePt-C films were investigated. The mask pattern was fabricated using self-assembly of di-block copolymers. For implantation, high- (40 keV for 14N+ and 100 keV for 40Ar+ ) and low- (7.5 keV for 14N+ and 4.5 keV for 40Ar+ ) energy 14N+ and 40Ar+ ions were used to modify the structural and magnetic properties of these films. The X-ray diffraction and transport of ions in matter simulations were performed for understanding the structural changes due to the ion implantations. These results revealed the conversion of face-centered tetragonal phase to face-centered cubic (FCC) phase for 40Ar+ ion implantations and increase in inter-planar spacing of FCC FePt (111) planes for 14N+ ion implantations. Magnetic properties were then probed by using a vibrating sample magnetometer (VSM), torque magnetometer, and magnetic force microscopy (MFM). The results from VSM and torque magnetometer showed a change in anisotropy from out-of-plane to in-plane directions for all the implantation cases except for low-energy 40Ar+ ion implantations. The MFM images also showed an absence of stripe domains confirming the above-mentioned effects.